Revalorización de la gastronomía de San Gabriel de Montúfar, Carchi - Pantoja Navarrete, Joffre Steven (2023)
The object of this research is the gastronomy of the city of San Gabriel de Montúfar, in the province of Carchi, Ecuador, consistent with the cultural identity and traditions that make the place unique, and that are attributes of the characteristic diversity of Ecuador that It stands out worldwide in accordance with the multiculturalism attribute of the model State established in the constitutional regulations, having as a general objective, the revaluation and highlight of the gastronomy of the city of San Gabriel de Montúfar, through a meticulous analysis of traditional gastronomic recipes, it is aim to enhance the uniqueness and authenticity of the characteristic dishes of the region. For this purpose, the methodology is used in accordance with the mixed qualitative and quantitative modality, using as a level of depth based on a descriptive study, and the inductive, deductive, analytical and synthetic methods\; As techniques, the survey, interview and digital catalog, applied based on instruments such as a questionnaire and interview guide, the application of these resources and their usefulness, their results are directed to give attention and answer to the question that constitutes the basis of this research. . . In relation to the results obtained, there are indicators and critical contributions that attribute the verification of the idea under investigation and the need and feasibility of the proposal for gastronomic revaluation of the city of San Gabriel, presented through a catalog of the main dishes. typical flavors that the city has, the unique and characteristic flavors, as well as their preparation, in such a way that it contributes to the rescue and preservation of the local culinary legacy, strengthening cultural identity and tourist positioning at a national and global level.